Relationship between protein intake and sarcopenia in older adults: A systematic review - Pérez-Cruz, Pedro Jesús (2025)
[Objective] Assess whether low protein intake is related to the development of sarcopenia in older adults. [Methods] This paper included primary studies focused on the relationship between protein intake and sarcopenia or its individual components (low muscle mass and strength and lower physical performance) in adults older than 60 years. The following studies were excluded: projects with no research design, studies with other nutritional interventions, and studies in older individuals with a sarcopenia diagnosis different than the one defined by the European Working Group on Sarcopenia in the Older People, with other comorbidities, or with pharmacological treatment. A systematic search was conducted in four databases, utilizing keywords in combination with Boolean operators. [Results] Out of the 15 studies included, 6 cross-sectional studies and 1 cohort study identified a significant association between low protein intake and an increased risk of sarcopenia, while 3 studies reported no significant association. Furthermore, 3 randomized controlled trials (RCTs) found no significant improvements in the sarcopenia-related components for the protein-supplemented intervention group compared to the control group. Only one randomized controlled study and one secondary data analysis study demonstrated significant improvements in muscle mass within the intervention group. [Conclusions] Low protein intake was significantly associated with a greater development of sarcopenia and lower muscle mass. This association was not observed on individual sarcopenia-related components.